Tetracycline use in children and knowledge of its oral implications among nursing mothers. Issue 3 (December 2020) - Enabulele, Joan E.; Chukwumah, Nneka M.; Enabulele, Osahon
Abstract: Introduction: Use of tetracycline has been associated with oral side effects. This study assessed the attitude and practice of tetracycline use in children and knowledge of its oral implications among nursing mothers. Method: This was a prospective, descriptive cross-sectional study of nursing mothers who brought their babies for routine infant immunization. A self-administered questionnaire which collated information regarding socio-demographic characteristics, knowledge, attitude and practice of tetracycline use in children and knowledge of the side effects and oral implications of tetracycline use was used for this study. Results: A total of 128 nursing mothers with 53.9% not sure if tetracycline is safe for use in children. 38.3% of the respondents had administered tetracycline to their children with 32.7% claiming it was prescribed by a medical doctor. There was a statistically significant association between occupation and use of tetracycline in children. Less than half (48.4%) of the respondents knew that the use of tetracycline in children can be associated with side effects. The most common side effect reported by the respondents was diarrhea (32.3%). Only 19.5% of the respondents knew that use of tetracycline in children could affect oral health. Conclusion: Despite the side effects associated with use of tetracycline, nursing mothers still administer it to their children with knowledge of oral implication of tetracycline use low. There is need for health education and dissemination of information on the use of tetracyclines and its side effects in young children to mothers to prevent the development of oral complications associated with its use.